Biofilm Formation of Staphylococcus Aureus in Multiple Sclerosis Patients and its Essential Role in the Pathogenicity of the Disease - Suhad Hassan Aubaid; Ekhlas Saddam Falih; Suhaib khalid Ibrahim (Journal of Techniques)
Background: Multiple sclerosis (MS) is a chronic inflammatory, autoimmune neurological disease of the central nervous system (CNS). One of the most important factors that lead to increased bacterial resistance to an antibacterial agent and also increase the severity of multiple sclerosis, is the capability of producing enterotoxins and biofilm.